PENGEMBANGAN BUKU AJAR BIOLOGI SMA KELAS XI SEMESTER II BERBASIS ARGUMEN TOULMIN PADA TOPIK SISTEM TUBUH MANUSIA DAN HEWAN - Ayu Sri Purwaningsih (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2019)
This study aims to develop products in the form of high school biology textbooks for class XI in the second semester based on Toulmin argument. Textbooks developed were reviewed based on the characteristic of Toulmin on textbooks, testing the content and construct validity by lecturers, teachers and the readability test by students. The type of this research is research and development (R and D) from Borg and Gall. Development research procedures include needs analysis, product planning, product development, product validation and legibility tests. The technical analysis of the development data includes describing the characteristic of textbooks seen from the Toulmin’s component in the form of claims, ground, warrant, backing, qualifier and rebbutal in the form of argument maps, validity tests by experts meet valid criteria seen from the aspects of validation assessment and legibility test meet the categories good seen from student’s reading responses. The result of the development research conducted, stated that the characteristic of Toulmin argument map in the form of C-G-W-B-Q-R, C-G-W-B or C-G-W. Validity results have very valid criteria in terms of content and construct validity by experts with an average score of 3.64. the readability test results of students in understanding the teaching material on the topic of human and animal body systems are stated in good category including 68% answering well and 32% answering very well. Based on the test results, it can be concluded that the development of high school biology textbooks in class XI in the second semester was based on Toulmin arguments on the topic of human and animal body systems that have fulfilled the quality of books which are seen based on characteristics, content validity and legibility test.